Implementasi Upaya Penghindaran Gharar dalam Transaksi Pasar Uang Syariah - Ismatul Aula; Ananda Rizki Aulia; Rina Widayanti; Tiara Nahda Wati; Muhammad Iqbal Sanjaya (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the implementation of gharar avoidance efforts in sharia money market transactions in Indonesia. The method used is qualitative through a literature review, by collecting data from literature, regulations, and documents related to gharar avoidance practices and strategies. The results of the study indicate that the implementation of clear sharia contracts, supervision from DSN-MUI and OJK, and the use of technology such as smart contracts and blockchain can minimize gharar elements in sharia money market transactions. Transparency and clarity of the main elements of the transaction, such as objects, prices, and time of delivery, are the main keys to avoiding uncertainty and potential losses for the parties. In addition, continuous improvement of sharia financial education and literacy also strengthens consumer protection and public trust. However, challenges remain, especially related to the low level of sharia financial literacy and the complexity of innovative financial products that have the potential to cause new gharar. Overall, efforts to avoid gharar are important to maintain the integrity and sustainability of the sharia money market, so that continuous strengthening of education, supervision, and technological innovation is needed so that the sharia money market becomes more credible and trusted by the public..